Housing and health: An empirical framework for refugee reception centres. (20th October 2021) - Hintermeier, M; Rast, E; Ziegler, S; Bozorgmehr, K; Biddle, L
Abstract: Background: Housing is a key social determinant of health. Newly arriving asylum seekers and refugees (ASR) in Germany are assigned to reception centres (RC), comprising large, shared facilities in remote locations. Our aim was to explore how housing affects health from the perspective of ASR in order to develop an empirical framework for further research. Methods: We conducted a secondary analysis of 47 qualitative interviews with ASR living in German RC and developed a multidimensional framework containing the effects of housing characteristics on health in this setting. An initial coding scheme with five dimensions was developed from the literature: material aspects, meaningful aspects, housing as an expression of socioeconomic status, community, and immediate environment. Using thematic analysis, sub-codes were generated inductively, resulting in the final framework. Results: Important material aspects included building structure, basic amenities, sharing of living space and food provision. Among these, room sharing and food provision were particularly relevant for participants. Meaningful dimensions important for health included autonomy, privacy, safety and stability, which were limited in RC due to missing door locks, room sharing, restrictions of movement and frequent transfers between centres. Based on participants' statements, the community was divided into "outside" and "inside" the RC, which, unlike the "outside" community, have collective and organisational characteristics. We subsumed statements about distances to services and amenities into immediate environment. However, participants reported that short distances did not always guarantee access. Conclusions: We identified important interdependent dimensions of housing which affect health and well-being among ASR and consolidated them into an empirical framework which can serve as a basis for further research, including the future development of measurement instruments to assess effects of housing on ASR health. Key messages: ASR narratives show that housing dimensions with importance for health in reception centres have specific characteristics and are interdependent. We developed a framework which can be used for further research on the effects of housing on ASR health in this setting, including the construction of quantitative measurement instruments.